Cultural diversity and inclusion in early years education - Borkett, Penny (Diversity and inclusion in the early years, 2018)
"Cultural Diversity and Inclusion in Early Years Education reveals how cultural diversity can be celebrated in every early years setting. Acknowledging the impact of culture on a child's development and identity, the book demonstrates the need for practitioners to appreciate cultural difference, value diversity, and ensure inclusive practices. Alongside comprehensive discussion of current and historical policy relating to multiculturalism, and relevant socio-cultural theory, the book provides practical guidance and resources to support practitioners in responding to the challenges of working with families and children from diverse cultural backgrounds. Chapters focus on topics such as: - policy and the role of the practitioner - socio-cultural theories relating to child development - building working relationships with families - the impact of culture on a child's identity - enabling environments and inclusive strategies. Including case studies, reflective questions, and suggestions for further reading and research, this essential book will help early years practitioners and students to embrace the varied cultural heritages of the children in their care" --Resumé vydavatele